RELATIONSHIP BETWEEN TOBACCO DEPENDENCE AND SCHIZOPHRENIA - Widhidewi, Wayan (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana, 2014)
Tobacco dependence in schizophrenia patients is a problem that got more concern, with few treatment options. Peoples with schizophrenia have a prevalence rate of cigarette smoking two until four times higher than the general population. Consequently, patients also have a lower smoking quit rate than the general population. Tobacco dependence in this population may complicate symptoms and also has adverse physiological effects on patients. Besides that, patients with schizophrenia tend to smoke more heavily than smokers in general population. This can increased smoking-related morbidity and mortality and impose a significant financial burden on patients. Recent studies demonstrated that patients with schizophrenia smoke before the onset of the illness and also start smoking earlier than the average population. Patients become psychotic earlier than patients who do not smoke, and require higher dose of anti-psychotic medications.
Keywords: schizophrenia, tobacco dependence, smoking, nicotine